2017
DOI: 10.1155/2017/8401518
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated with the Prevalence of Thyroid Nodules and Goiter in Middle-Aged Euthyroid Subjects

Abstract: The aim of the present study was to determine associations of thyroid hormone levels and different metabolic parameters and anthropometric measurements with volume of nodular and nonnodular thyroid as well as with prevalence of goiter and thyroid nodules in middle-aged euthyroid subjects. Methods. The study consisted of 317 euthyroid subjects aged 48-49 from the Kaunas Cardiovascular Risk Cohort study. Thyroid-stimulating hormone (TSH), free thyroxine (FT4), and antithyroid peroxidase antibody (ATPO) levels, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
34
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 47 publications
(56 reference statements)
14
34
2
4
Order By: Relevance
“…A positive association serum TSH elevation was confirmed by several researchers (Díez and Iglesias, 2011;Kitahara et al, 2012;Knudsen et al, 2005;Reinehr, 2011;Rotond et al, 2009;Solanki et al, 2013;Váldes et al, 2017), and recently, higher TSH concentrations were considered as an independent risk factor for thyroid nodules (Dauksiene et al, 2017). However, this study showed no significant difference in TSH values between severely obese and nonobese patients with nodules.…”
Section: Discussionsupporting
confidence: 65%
“…A positive association serum TSH elevation was confirmed by several researchers (Díez and Iglesias, 2011;Kitahara et al, 2012;Knudsen et al, 2005;Reinehr, 2011;Rotond et al, 2009;Solanki et al, 2013;Váldes et al, 2017), and recently, higher TSH concentrations were considered as an independent risk factor for thyroid nodules (Dauksiene et al, 2017). However, this study showed no significant difference in TSH values between severely obese and nonobese patients with nodules.…”
Section: Discussionsupporting
confidence: 65%
“…The published reports have documented increasing thyroid volume with increasing BMI (7,8,19). Changes in body composition might affect thyroid volume.…”
Section: Discussionmentioning
confidence: 98%
“…The increased usage and experience with ultrasound of the neck resulted in detection of more incidental and nonpalpable thyroid nodules [11]. The prevalence of thyroid nodules ranges between 19% and 68% in patients who underwent random ultrasonography of the neck [4]. This high prevalence of thyroid nodules requires an evidence-based approach for appropriate diagnosis and management which may lead to reduction of the unnecessary surgical intervention and its associated complications [1].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the prevalence of palpable nodules on physical examination alone in adult population is as low as 5-7% [3]. On the other hand, thyroid nodules are frequently detected upon neck ultrasonography which ranges from 19% to 67%; of which only 4-7% are also palpable on physical examination [4]. The reported prevalence of thyroid nodules in some studies is as high as 68% using high-resolution ultrasound in randomly chosen subjects [5].…”
Section: Introductionmentioning
confidence: 99%